2010
DOI: 10.2298/fil1001087u
|View full text |Cite
|
Sign up to set email alerts
|

Warped product CR-submanifolds of LP-cosymplectic manifolds

Abstract: In this paper, we study warped product CR-submanifolds of LP-cosymplectic manifolds. We have shown that the warped product of the type M = N T × f N ⊥ does not exist, where NT and N ⊥ are invariant and anti-invariant submanifolds of an LP-cosymplectic manifoldM , respectively. Also, we have obtained a characterization result for a CR-submanifold to be locally a CRwarped product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Since M is proper, then cos 2 θ 2 0, thus from (20) we conclude that f is constant. Hence, the theorem is proved completely.…”
Section: Warped Product Bi-slant Submanifoldsmentioning
confidence: 83%
See 2 more Smart Citations
“…Since M is proper, then cos 2 θ 2 0, thus from (20) we conclude that f is constant. Hence, the theorem is proved completely.…”
Section: Warped Product Bi-slant Submanifoldsmentioning
confidence: 83%
“…Warped product submanifolds have been studied rapidly and actively, since Chen introduced the notion of CR-warped products of Kaehler manifolds [10,11]. Different types of warped product submanifolds have been studied in several kinds of structures for last fifteen years (see [2,15,18,20,22]). The related studies on this topic can be found in Chen's book and a survey article [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the non-definitive nature of the Riemannian metric, the geometry of warped product submanifolds with more general non-degenerate metric (i.e., positive as well as negative definite metric) became a topic of investigation. In light of that, many authors discussed the existence and nonexistence of such warped product submanifolds in Lorentzian settings [33,42]. Recently, Chen and Munteanu [13], the authors of [30,31] and Aydin and Cöken [2] initiated the study of the geometry of pseudo-Riemannian warped products submanifolds in para-Kähler manifolds, paracontact manifolds and slant submanifold in semi-Riemannian manifolds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Again Atceken [2] studied warped product semi-slant submanifolds in Kenmotsu manifolds. Beside these, Uddin and his co-authors studied warped product submanifolds in different context such as ( [13], [28]) etc. Recently, Hui and Atceken [10] studied warped product semi-slant submanifolds of (LCS) n -manifolds.…”
Section: Introductionmentioning
confidence: 99%